PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT. SEWU SEGAR PRIMATAMA JAKARTA SELATAN - Andi Sopandi (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2022)
The purpose of this study was to determine the effect of work discipline and work motivation on employee performance at PT. Sewu Segar Primatama either partially or simultaneously. This type of research used is quantitative. The population in this study were employees of PT. Primatama Fresh Sewu. The sampling technique used was saturated sampling technique and the samples in this study were 62 respondents. The data collection technique is a questionnaire, while the data analysis uses validity tests, reliability tests, classical assumption tests, simple and multiple linear regression analysis, coefficient of determination analysis and hypothesis testing. The results of this study indicate that Work Discipline has a positive and significant effect on employee performance, this can be seen from the results of the t-test on the work environment variable of 6.846 with a significant value of 0.000. Work Motivation has a positive and significant effect on employee performance, this can be seen from the results of the t-test on the motivation variable of 4.643 with a significant value of 0.000. Work Discipline and Work Motivation have a simultaneous and significant effect on employee performance, this can be seen from the results of the f-test of 43,651 with a significant value of 0.000 and the f-table of 3.18. Work Discipline and Work Motivation affect employee performance by 62.1%, this is based on the acquisition of an R-Square of 0.621 or 62.1%. While the remaining 37.9% is influenced by other factors not examined.